Global Idea Sourcing: An Empirical Investigation into the Mechanisms Behind the Usage of Foreign Business Sources for Innovation - Wolfgang Sofka (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
Globalization has set new paradigms, especially in the business world. Breakthroughs in technology (telecommunications, logistics, the internet) and ideology (most notably economic and political trends in China and India) are creating exciting opportunities as well as crucial challenges. This paper analyses one of the core aspects of competitiveness: a firm?s ability to innovate in a globalized environment. We question whether it is universally advantageous to directly invest abroad and argue instead that a company may use its international value chain (customers, suppliers and competitors) to utilize foreign sources for innovation at home. We suggest a combination of three factors to identify and explain such innovation strategies: access, need and absorptive capacities. Our empirical analysis rests upon a broad data sample of almost 2,300 German companies for which we devised a trivariate probit model. In essence, we find a market-seeking strategy for using foreign customers as a source for innovation that is more beneficial to standardized products and becomes more feasible if the lead status of domestic customers is limited. What is more, internalizing this link with foreign customers becomes preferable as their importance as a driver of sales increases. For foreign suppliers we identify a risk-sharing and technologyseeking strategy as a reaction to more dynamic domestic markets and a less favorable domestic environment in both research and regulation. Hence, companies optimize or augment their innovation activities by invoking ideas from foreign suppliers. Then again, companies rely on foreign competitors for technology-seeking as those sources become more readily available and crucial in international competition.
Keywords: F23; O32; O31; 330; innovation strategy; globalization; external sources; Innovationsmanagement; Innovation; Wertkette; international; Deutschland